Estimasi Biaya Konstruksi Menggunakan Metode Parameter Pada Proyek Pemeliharaan Berkala Jalan Di Kota Manado - Eman, Peter A.; Lintong, Elisabeth M.; Jansen, Freddy (Sam Ratulangi University, 2018)
Cost estimation plays an important role in the implementation of construction projects. Activityestimation is one of the main processes in a construction project to know the amount of funds that mustbe provided for a building. In general, a construction project costs a lot. The inaccuracies that occur inthe supply will be less good to the parties involved. However, the owner of the project requires costestimation in order to prepare the project budget. In estimating the initial cost of the periodicmaintenance project the road still uses a simple way. The most commonly used method is to estimatethe road length parameters, ie by calculating the periodic maintenance cost of the road for every 1 kmof road length based on the previous project data. So that with the budget available the owner of theproject (owner) can provide long information path that will get regular maintenance activities. The length of a road segment shows the physical characteristics and size of a periodic roadmaintenance project that in practicality this information can be readily available in the early stages ofproject planning. Along with the need for efficiency, it is necessary to develop techniques for making asimple cost estimation model. What is important in the cost estimation model in the early stages ofproject planning is to be quick, easy to use, accurate and generate reliable estimates. The aims of this research are to produce the project cost estimation model of periodic roadmaintenance for the relationship between Total Project Cost and LPA volume and ACWC volume, To produce a project cost estimation model of periodic road maintenance for the relationship betweenthe Total Project Cost and the ACWC volume and to produce the project cost estimation model ofperiodic road maintenance for the relationship between Total Project Cost and LPA volume. The method used are parameter method. Based on the results of the analysis that has been done, itcan be concluded in order to estimate the cost of the periodic maintenance project of roads in Manadacity, in accordance with the research objectives as follows: The project cost estimation model for therelationship between Total Project Cost of Routine Road Maintenance with LPA volume and ACWCvolume is as follows: Total Cost = 2373898,22 LPA + 115476,64 ACWC + 283033186,7 withcorrelation value equal to 94,70% and determination value equal to 89,70%. The project cost estimationmodel for the relationship between the Total Cost of the Road Maintenance Project Period with ACWCvolume ie: Total Cost = 186688,461 ACWC + 699100355,10 with r = 89,90% and r2 = 80,80%. Theproject cost estimation model for the relationship between Total Project Cost of Routine RoadMaintenance with LPA volume ie: Total Cost = 4567920,593 LPA + 30710896,10 with correlationvalue of 87.40% and determination value of 76.40%.Keywords: cost estimation, parameter method, total project cost, road routine maintenance.